2013
DOI: 10.1371/journal.pone.0065423
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Rate versus Low Dose Rate Brachytherapy for Oral Cancer – A Meta-Analysis of Clinical Trials

Abstract: ObjectiveTo compare the efficacy and safety of high dose rate (HDR) and low dose rate (LDR) brachytherapy in treating early-stage oral cancer.Data SourcesA systematic search of MEDLINE, EMBASE and Cochrane Library databases, restricted to English language up to June 1, 2012, was performed to identify potentially relevant studies.Study SelectionOnly randomized controlled trials (RCT) and controlled trials that compared HDR to LDR brachytherapy in treatment of early-stage oral cancer (stages I, II and III) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…To be able to deliver the HDR brachytherapy in a short overall time most institutions use 2 fractions per day with a minimum of 6 h interval that is the time required to allow complete repair of sublethal damage. A metanalysis did not reveal significant differences in outcome compared to LDR, but the data need to be interpreted with caution [17]. Table 1 gives an overview of proposed fractionation schedules for PDR and HDR.…”
Section: General Aspects Of Treatment Planning: Dose and Fractionationmentioning
confidence: 96%
See 1 more Smart Citation
“…To be able to deliver the HDR brachytherapy in a short overall time most institutions use 2 fractions per day with a minimum of 6 h interval that is the time required to allow complete repair of sublethal damage. A metanalysis did not reveal significant differences in outcome compared to LDR, but the data need to be interpreted with caution [17]. Table 1 gives an overview of proposed fractionation schedules for PDR and HDR.…”
Section: General Aspects Of Treatment Planning: Dose and Fractionationmentioning
confidence: 96%
“…Complications of the technique include soft tissue necrosis and bone necrosis in 10-30% of the implants using HDR. Meta-analysis of 6 trials constituting 1 randomized trial and 5 controlled trials with 607 patients (LDR = 442, HDR = 160) revealed no statistically significant differences between LDR and HDR in terms of local recurrence, overall mortality and grade 3/4 complications [17]. PDR brachytherapy has also been reported to result in outcomes comparable to that of LDR [16].…”
Section: Oral Cavity Cancermentioning
confidence: 99%
“…A recent meta-analysis of published data indicated that HDR brachytherapy is a comparable alternative to LDR brachytherapy in the treatment of oral cancer. The authors suggest: HDR brachytherapy might become a routine choice for early-stage oral cancer in the future [ 44 ]. Furthermore, data in the literature also underline the fact that neither young nor old age are negative prognostic factors for outcomes with brachytherapy in oral cancer [ 45 , 46 ].…”
Section: Oral Cavitymentioning
confidence: 99%
“…Due to the necessity of performing visually controlled application, brachytherapy in this area is only possible in case of lip cancer, oral cavity cancer, selected neoplasms of nasopharynx, nasal cavity and nasopharynx, as well as in case of repeated radiotherapy of nodular relapses in the head and neck area [7, 8, 9, 10, 11, 12, 13, 14]. …”
Section: Discussionmentioning
confidence: 99%